2022
DOI: 10.1177/03000605221088560
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the Sharp score of 1057 patients with rheumatoid arthritis and anemia: a retrospective study

Abstract: Objective This study examined the relationship of the Sharp score with demographic factors and clinical immune-inflammatory markers in patients with anemia in rheumatoid arthritis (RA). Methods The clinical data of 1057 patients with RA and anemia and 1006 patients with RA without anemia were retrospectively analyzed. Spearman’s correlation coefficient analysis, association rule analysis, and logistic regression were used to study the relationships between the Sharp score and influencing factors in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A retrospective examination spanning two decades revealed that as many as 29.4% of 34 neonatal lupus erythematosus cases were accompanied by anemia 41 . Similarly, another retrospective investigation ascertained that the anemia incidence rate soared to 51.24% among 1057 patients a icted with rheumatoid arthritis 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective examination spanning two decades revealed that as many as 29.4% of 34 neonatal lupus erythematosus cases were accompanied by anemia 41 . Similarly, another retrospective investigation ascertained that the anemia incidence rate soared to 51.24% among 1057 patients a icted with rheumatoid arthritis 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the prevalence of anemia in RA is related to the prognosis of patients. For the parameters to be evaluated, including swelling, joint pain and activity level, there is a positive correlation between the improvement of symptoms and the relief of anemia [ 15 , 16 ]. Previous studies [ 17 , 18 ] have shown that the quality of life score of RA patients is significantly improved after anemia treatment, RA patients with anemia may have more severe joint disease, and if anemia is successfully treated, joint disease may also be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is a relatively common clinical expression of RA, influencing 30–70% of patients. 23 Anemia is closely related to the disease activity of RA and can be served as predicting incipient joint damage of RA. 24 The level of Hb104.50 (89.75–119.50)g/L in RA with HC group was lower than the level of Hb110.00 (98.00–121.00)g/L in RA without HC group, and anemia was more serious, which suggested that HC might correlate with disease activity of RA.…”
Section: Discussionmentioning
confidence: 99%